2021
DOI: 10.2174/1871527320666210126113848
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Abnormal c-JNK/p38MAPK Signaling in Amyotrophic Lateral Sclerosis: Potential Drug Targets and Influences on Neurological Disorders

Abstract: : c-JNK (c-Jun N-terminal kinase) and p38 mitogen-activated protein kinase (MAPK) family members work in a cell-specific manner to incorporate neuronal signals that cause glutamate excitotoxicity, impaired protein homeostasis, defective axonal transport, and synaptic dysfunctions. Consistent with the importance of these cellular events in the up-regulation of c-JNK/p38MAPK signaling is associated with neurodegenerative diseases in various clinical and pre-clinical studies. Exceptionally, a large number of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 137 publications
0
11
0
Order By: Relevance
“…The initiation of this pathway followed by the activation of microglia cells and onset of the MAPK signaling cascade results in inflammation of the neurons. [ 114 ] p38 kinase activity is firmly linked to motor neuron degeneration in animal models of ALS. The results have shown that MLT can effectively reduce the phosphorylation of p38.…”
Section: Anti‐inflammatory Effects Of Mlt On Various Diseasesmentioning
confidence: 99%
“…The initiation of this pathway followed by the activation of microglia cells and onset of the MAPK signaling cascade results in inflammation of the neurons. [ 114 ] p38 kinase activity is firmly linked to motor neuron degeneration in animal models of ALS. The results have shown that MLT can effectively reduce the phosphorylation of p38.…”
Section: Anti‐inflammatory Effects Of Mlt On Various Diseasesmentioning
confidence: 99%
“…Overactivation of JNK/p38 signaling has been observed in demyelination and neuroinflammation (Singh et al, 2021). Downregulation of c-JNK/p38MAPK can promote oligodendrocyte regeneration and prevent mitochondrial dysfunction, microglia survival, and neurotransmitter recovery (Yadav et al, 2021b). Activation of p65 in astrocytes and microglia appears to favor demyelination, while its inhibition supports remyelination (Blank & Prinz, 2014).…”
Section: The Effect Of Oz On Proinflammatory Cytokines and Anti-infla...mentioning
confidence: 99%
“…Protein kinases are the modulators of various signaling cascades and govern major functions of cellular homeostasis. Kinase overexpression is associated with various human diseases ( Borgo et al, 2021 ; Lee and Paull, 2021 ), including cancers and neurodegenerative disorders ( Yadav et al, 2021 ). Recent findings have unravelled kinases as therapeutic markers and urged the development of potent and selective inhibitors against kinases.…”
Section: Kinases Associated With Cancer and Neurodegenerationmentioning
confidence: 99%